Analysis of 270/290/330-nm AlGaN-Based Deep Ultraviolet Light-Emitting Diodes With Different Al Content in Quantum Wells and Barriers - G. F. Yang; Q. Zhang; J. Wang; S. M. Gao; R. Zhang; Y. D. Zheng (IEEE Photonics Journal, 2015)
The optical and electrical properties of 270/290/330-nm AlGaN-based deep ultraviolet (UV) light-emitting diodes (LEDs) with different Al content in quantum wells and barriers have been investigated systematically. Based on the experimental and numerical study, it is observed that the UV LEDs with longer wavelength and lower Al composition in AlGaN multiple quantum wells (MQWs) possess less dislocation density, higher light output power, and external quantum efficiency. Large ideality factors calculated from the I–V curves and simulated energy band profiles indicate that the current in the deep UV LEDs with high Al content is dominated by tunneling mechanism, which is attributed to the resulting potential drop in the active region caused by large polarization field in AlGaN MQWs.